Asymptomatic Bochdalek's Hernia in an Adult: A Case Report - Lochman, Petr; Hůlek, Michal; Dušek, Tomáš (Curēus, 2024)
Bochdalek's hernia is the most common congenital malformation of the diaphragm with a defect in its posterolateral part. Its clinical manifestation in adulthood is rare. It is often an incidental finding, and its diagnosis may be challenging. A high index of suspicion is necessary, especially in cases presenting with cardiopulmonary or abdominal symptoms and an ambiguous finding on the initial chest X-ray. We present a case of an asymptomatic 50-year-old male patient with a bulky left-sided Bochdalek's hernia. Surgical treatment was indicated, and a direct suture of the defect after reduction of the herniated greater omentum, transverse colon, and tail of the pancreas was performed from the upper midline laparotomy. The postoperative course was uneventful, and the patient was discharged on the fifth postoperative day. The management of adult patients with these kinds of hernias in both acute and chronic settings is discussed, and some recommendations are mentioned to minimize unnecessary pitfalls.